Baseball without borders : the international pastime - Gmelch, George (University of Nebraska, 2006)
A televised baseball game from Puerto Rico, Japan, or even Cuba might look a lot like the North American game. This book looks at how the game was imported - how it took hold and developed, how it is organized, played, and followed - and what these local and regional trends and features say about the sport's place in particular cultures.